INFLUENCE OF DEEP WATER RUNNING PRACTICE IN PEOPLE BEARERS OF CHRONIC DISEASE OBSTRUCTIVE (Fiep Bulletin - online, 2013)
Chronic Obstructive Pulmonary Disease (COPD) is for damages airways and smokers are more likely to acquire this disease. Symptoms appear only after thirty years when lung capacity is already compromised. This study aimed to analyze the liquid medium, particularly the Deep Water Running (DWR) potentiating agent may be a quality of life of COPD patients. The sample consisted of 6 patients, 4 women and 2 men. There were 25 classes DWR, taking 45 minutes in three months. There were two assessments: pre-and post-training for the following variables (weight, height, Body Mass Index, measures Circles, localized muscle strength) than the protocol of Activities of Daily Living.
Keywords: COPD; Smoking and AVD